Царица Савская и Соломон - Обермайер Зигфрид (Женские лики - символы веков, 2009)
Экземпляры: ф.6 (20171227) / Инвентарный номер: 2120 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: О-13 / ГРНТИ: 17.82.31 / ББК: 84(4Гем)-44